Sense of place and certainty in uncertain socioeconomic conditions: Contributions of local cuisine to culinary tourism. - Duarte Alonso, Abel; Kok, Seng (Taylor and Francis, 2020)
This study examines the extent to which local cuisine helps shape a sense of place and its contribution to adapting to uncertain socioeconomic conditions. By adopting entrepreneurial action theory, and through its associations with the findings, the study proposes a framework illustrating the significance of the above themes in the context of Peru's gastronomy. The data are based on interviews with 14 restaurant owners-managers operating in the city of Lima, Peru. This approach was further complemented by on-site observations, and by archival data of businesses (company websites, printed information). The findings reveal alignment with both stages of entrepreneurial action, predominantly through opportunity attention, which emphasises recognising and acting upon opportunities in general. This stage became apparent through comments underlining the significance of local gastronomy in contributing to sense of place. Similarly, opportunity attention arose in comments highlighting the potential of local gastronomy as a tool for socioeconomic development.